1986
DOI: 10.1111/j.1528-1157.1986.tb03497.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anticonvulsant Activity and Neurotoxicity of Felbamate and Four Prototype Antiepileptic Drugs in Mice and Rats

Abstract: Felbamate (2-phenyl-1,3-propanediol dicarbamate), phenytoin, phenobarbital, ethosuximide, and valproate were evaluated in mice and rats with a battery of well-standardized anticonvulsant test procedures. The results obtained indicate that felbamate exhibits a wider range of experimental anticonvulsant activity than either phenytoin or ethosuximide and a somewhat more restricted range than either phenobarbital or valproate. Felbamate is effective in nontoxic intraperitoneal doses in mice by the maximal electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
5

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 9 publications
2
93
0
5
Order By: Relevance
“…19,37 Increasing GABA release could be a potential mechanism through which gabapentin prevents NRHypo neurotoxicity because a wide range of GABAergic agents are known to prevent NRHypo neurotoxicity. 13,26,38 While ethosuximide does prevent NRHypo neurotoxicity, it does so at a dose (ED 50 = 336 mg kg −1 ) that is approximately 10-fold greater than that needed to prevent pentylenetetrazol-induced seizures (ED 50 = 54 mg kg −1 ), 27 suggesting that its mechanism of action is different in the two model systems. Since its suspected mechanism of action against pentylenetetrazolinduced seizures is inhibition of T-type calcium currents, 19 we tentatively conclude that inhibition of this type of calcium current is not an efficacious method of preventing NRHypo neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,37 Increasing GABA release could be a potential mechanism through which gabapentin prevents NRHypo neurotoxicity because a wide range of GABAergic agents are known to prevent NRHypo neurotoxicity. 13,26,38 While ethosuximide does prevent NRHypo neurotoxicity, it does so at a dose (ED 50 = 336 mg kg −1 ) that is approximately 10-fold greater than that needed to prevent pentylenetetrazol-induced seizures (ED 50 = 54 mg kg −1 ), 27 suggesting that its mechanism of action is different in the two model systems. Since its suspected mechanism of action against pentylenetetrazolinduced seizures is inhibition of T-type calcium currents, 19 we tentatively conclude that inhibition of this type of calcium current is not an efficacious method of preventing NRHypo neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ethosuximide was effective in preventing NRHypo neurotoxicity (Figure 4), but its ED 50 of 336 mg kg −1 was 10-fold greater than that reported to be needed to treat pentylenetetrazol-induced seizures. 27 We could not carry out an analysis of its ED 50 ratios because ethosuximide is inactive in the MES seizure model.…”
Section: Other Aedsmentioning
confidence: 99%
“…FBM has been demonstrated to be efficacious in a large spectrum of in vivo epilepsy animal models. In rodents, FBM inhibits seizures induced by maximal electroshock, by picrotoxin, pentylentetrazol and 4-aminopyridine, but not by bicuculline or strychnine (Swinyard et al, 1986; for review see Burdette & Sackellares, 1994). In Rhesus monkeys, FBM reduced seizures produced by aluminium hydroxide injections into cortical regions (Lockard et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…(64), having a broader spectrum of anticonvulsant activity than phenytoin or ethoswimide. Though its exact mechanism of action is undefined, predinical evaluations have indicated that felbamate appears to increase seizure threshold and prevent seizure spread (65). In controlled clinical studies, felbamate has demonstrated efficacy as adjunctive therapy in the treatment of partial and generalired seizures in adults (66)(67)(68).…”
Section: New Antiepileptic Medicationsmentioning
confidence: 99%